2015
DOI: 10.1556/036.102.2015.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heat provocation tests on the human gingiva: the effect of periodontal disease and smoking

Abstract: Periodontal inflammation is associated with morphological changes in the blood vessels which may influence the regulation of gingival blood flow (GBF). Our aim was to adapt the heat provocation test to the human gingiva to assess vascular reactivity in periodontal inflammation. Method: GBF was recorded by Laser Doppler Flowmetry before and after heat provocation in healthy volunteers (n = 50). Heat was generated either by warm saline or a halogen lamp. The latter method was also utilized for a heat test in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 58 publications
2
21
0
3
Order By: Relevance
“…Vasodilation ends within 60 seconds in other tissues, contrary to our study, in which it was sustained for more than 10 minutes in the Nitro POHL group and lasted longer than the observation period (14 minutes) in the Nitromint group. The extended hyperaemia is in line with our other observations in the human gingiva, where hyperaemia after short‐time occlusion or after heat provocation lasted much longer than in other tissues, suggesting a high reactivity of the gingiva.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Vasodilation ends within 60 seconds in other tissues, contrary to our study, in which it was sustained for more than 10 minutes in the Nitro POHL group and lasted longer than the observation period (14 minutes) in the Nitromint group. The extended hyperaemia is in line with our other observations in the human gingiva, where hyperaemia after short‐time occlusion or after heat provocation lasted much longer than in other tissues, suggesting a high reactivity of the gingiva.…”
Section: Discussionsupporting
confidence: 91%
“…But extent of the vasodilatory effect was very similar to the previous data. In these studies, thermal provocation of the gingiva or post‐occlusive reactive hyperaemia test were applied in which NO has a significant role in the vasodilatory mechanism . These indicate that the locally released NO from nitroglycerin in this study could be close to the physiological levels.…”
Section: Discussionmentioning
confidence: 80%
“…The underlying mechanisms of smoking and its effect on gingival bleeding are somewhat unclear. There is limited evidence that tobacco smoke promotes gingival vasoconstriction in humans . There is some evidence of tobacco‐induced suppressed angiogenesis, where a reduced number of gingival vessels or vessels of smaller caliber have been found in smokers relative to non‐smokers .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Molnar et al. have shown that the gingiva of smokers are less responsive to a heat provocation test, which assesses vascular reactivity, than nonsmokers, as measured by induction of gingival crevicular fluid (GCF) flow . Interestingly, the authors reported that, independent of periodontal disease classification, the volume of GCF produced is significantly lower in smokers compared with nonsmokers.…”
Section: Suppressed Gingival Bleeding In Tobacco Smokersmentioning
confidence: 99%